The Influence of Transcendentalism through Herman Melvilleâ€™s Short Story, â€œBartleby the Scrivenerâ€ - Napitupulu, Rita; Angginata, Stefany (Budapest International Research and Critics University, 2022)
The objectives of the research are 1) to analyze the influence of transcendentalism, through Herman Melvilleâ€™s short story,â€Bartleby the Scrivenerâ€ and 2) to analyze why transcendentalism influences Herman Melville, through the short story, â€ BartlebyÂ the Scrivener. The methodology used by the researcher is the qualitative research that deals with data that are in the form of words or pictures rather than numbers and statistics and use the qualitative data analysis, that it is as â€œworking with data, organizing it, breaking it into manageable units, synthesizing it, searching for patterns, discovering what is important and what is to be learned, and deciding what you will tell others. Through the analysis, the researcher finds that, the first Herman Melville portrays Bartleby who resists the Lawyer, his master, while he himself as a worker for the law office, the second, he portrays the place where Bartleby is working, which is tame and deficient, as the landscape painters call that there is no life there. The third, he portrays the three nicknames given is dehumanizing because those three nick names, Turkey, Nippers, Ginger Nut are not the humanâ€™s names. Thatâ€™s how transcendentalism influences Herman Melville. Due to the portrayals explained by the researcher above, then researcher finds that why transcendentalism influences Herman Melville with the book he created is as a tool of criticism.